Magnetic glass in shape memory alloy : Ni 45 Co 5 Mn 38 Sn 12 - Lakhani, Archana (2013)
The first order martensitic transition in the ferromagnetic shape memory alloy Ni45Co5Mn38Sn12 is also a magnetic transition and has a large field induced effect. While cooling in the presence of a field this first order magnetic martensite transition is kinetically arrested. Depending on the cooling field, a fraction of the arrested ferromagnetic austenite phase persists down to the lowest temperature as a magnetic glassy state, similar to the one observed in various intermetallic alloys and in half doped manganites. A detailed investigation of this first order ferromagnetic austenite (FM-A) to low magnetization martensite (LM-M) state transition as a function of temperature and field has been carried out by magnetization measurements. Extensive cooling and heating in unequal field (CHUF) measurements and a novel field cooled protocol for isothermal MH measurements (FC–MH) are utilized to investigate the glass like arrested states and show a reverse martensite transition. Finally, we determine a field–temperature (HT) phase diagram of Ni45Co5Mn38Sn12 from various magnetization measurements which brings out the regions where thermodynamic and metastable states coexist in the HT space, clearly depicting this system as a 'magnetic glass'.